Relationship Between Workplace Humor, Compassion, and Quality of Work Life Among Hospital Nurses - Kriselda Safhira; Yohanes Budiarto; P. Tommy Y. S. Suyasa (Dinasti Publisher, 2024)
Quality of Work Life (QWL) encompasses factors that shape employee satisfaction, well-being, and happiness in the workplace. This study examines the relationship between quality of work life and humor types in the workplace, with compassion as a moderating variable. Humor is conceptualized as verbal and non-verbal communication that elicits cognitive or affective responses, while compassion reflects sensitivity to the suffering of others, coupled with a desire to alleviate it. The sample consisted of 179 hospital nurses in the Jabodetabek area who completed questionnaires assessing the quality of work life, humor types, and compassion. Data analysis using SPSS 22 revealed that positive humor, such as self-enhancing and affiliative humor, was related to quality of work life, whereas negative humor, such as self-defeating and aggressive humor, showed no significant relationship. Compassion moderated the relationship between positive humor and quality of work life. These findings highlight the importance of fostering compassion in hospital nurses to enhance their quality of work life.